Empowerment of Pregnant Women - Leila HajiPour; Monirosadat Hosseini Tabaghdehi; Zahra TaghiZoghi; Zohreh Behzadi (Journal of Holistic Nursing and Midwifery)
Introduction: Empowerment during pregnancy is defined as a sense of self- fulfillment and increased independence, promotion of interaction with individuals and environment leading to an increase in the spontaneous psychological energy to achieve successful pregnancy and childbirth. Education during pregnancy empowers women for better adjustment confronting physical and emotional changes associated with pregnancy and experiencing a satisfying delivery. Objective: Present study was conducted to determine the empowerment of pregnant women referring to Tonekabon health centers. Methods: This cross-sectional study was conducted on 200 pregnant women who referred for prenatal care clinics to in Tonekabon in 2013. Pregnant women participating in the study were at least literate and had no significant medical problems or obstetrical pregnancy indicating a high-risk pregnancy. Besides, they had no history of previous cesarean section and gave consent to participate in the study. Cluster sampling method was used. Two centers of clusters were randomly selected. All pregnant women referring to these two centers for prenatal care were included after obtaining the written consent. The data collection tool was a questionnaire designed in two parts. The first part contained demographic and obstetric information and the second part was pregnant women's empowerment questionnaire by Kameda, with 27 questions in five dimensions; Self-efficacy (6 questions), future image (6 questions), self- esteem (7 questions), support and assurance from others (4 questions), and joy of an addition to the family (4 questions) which were answered based on the Likert scale from strongly disagree to strongly agree with 1 to 4. Minimum score of 27 and maximum score of 108 were given to the answers. The mean score was used to judge about the answers. The data were analyzed using descriptive statistics and ANOVA (given the normal distribution of data) at significance level of 95% and p=0.05. Data collection was performed after approval by the Research Council of Azad University, Tonekabon Branch. Results: The mean age of subjects was 26.38 ± 3.76 years old. 36% of women were in their first trimester of pregnancy. The majority of pregnant women (55.55%) experienced their first pregnancy and had high school education (40%) and wanted pregnancies (79.5%). 90.5% of them were homemaker. This study found the mean and standard deviation of empowerment as 78.74 ± 6.71 (Minimum score 27 and maximum score 108). Of all empowerment dimensions, the highest mean score dedicated to self-esteem (19.19 ±1.82) and the lowest to the support and assurance from others (12.70± 1.59) and joy of an addition to the family (13.66 ± 1.79). The results showed a significant correlation between mother's education and empowerment score (p= 0.03). Moreover, the relationship between interest to continue the pregnancy and empowerment was statistically significant (p=0.005). No significant difference was observed between other variables such as pregnancy age, mother's age and number of pregnancy, mother's job and support of spouse, level of income and unwanted pregnancy and total score of empowerment. Conclusion: The findings of this study can be effective in assessment of prenatal care, planning and implementing delivery preparation classes and promotion of empowerment of pregnant women. Given the role of education in promoting women's empowerment it is suggested that the effect of natural childbirth in empowering pregnant women be considered in future studies. Prenatal education brings about positive feelings, happiness in the family, promoted ability to deal with new conditions, promoted maternal and newborn health, increased confidence, satisfaction of having children, active participation of family members in maintaining family health and promoted ability to adapt and cope with the problems and responsibilities of life.